DARK MATTER AND DARK ENERGY IN THE COMA CLUSTER OF GALAXIES - Bisnovatyi-Kogan, G. S.; Chernin, A. D. (Одеські астрономічні публікації, 2013)
The Coma cluster of galaxies is studied as a giant aggregation of dark matter and baryons embedded in the dark energy background. Key theory relations for the local dark-energy effects are given. On the basis of the theory and current observational data, three characteristic masses of the Coma cluster are introduced and evaluated. A new dark matter mass profile is suggested and used to find the upper bounds on the total mass and total size of the cluster. A solution is obtained for the hydrodynamic outflow of the polytropic gas from the gravitating center, in presence of the uniform Dark Energy (DE). The main property of the wind in presence of DE is its unlimited acceleration after passing the critical point. In application of this solution to the winds from galaxy clusters we suggest that collision of the strongly accelerated wind with another galaxy cluster, or with another galactic cluster wind could lead to the formation of a highest energy cosmic rays